2023
DOI: 10.1002/hsr2.1111
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and clinical outcomes among patients with COVID‐19 disease: A cohort study

Abstract: Background and Aims Thrombocytopenia is increasingly recognized among patients with critical illness and plays a role in several diseases affecting different organ systems. Therefore, we studied the prevalence of thrombocytopenia among hospitalized COVID‐19 patients and its correlation with disease severity and clinical outcomes. Methods This was an observational retrospective cohort study conducted on 256 hospitalized COVID‐19 patients. Thrombocytopenia is defined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…This exacerbates the inflammatory responses and renal impairment [32]. Lower platelet counts are associated with AKI [33]. Our study found a J-shaped association between the SII and SA-AKI, with higher mortality in the Q1 group than in the Q2 control group, although the difference was not statistically significant.…”
contrasting
confidence: 44%
“…This exacerbates the inflammatory responses and renal impairment [32]. Lower platelet counts are associated with AKI [33]. Our study found a J-shaped association between the SII and SA-AKI, with higher mortality in the Q1 group than in the Q2 control group, although the difference was not statistically significant.…”
contrasting
confidence: 44%
“…33.3% (3/9) of TMA patients developed AKI. Alkhalifa et al noted that thrombocytopenia was closely linked with and significantly predicted AKI 6 . Our results seem to confirm their observation; in fact, AKI in patients with COVID-19 is common, and COVID-19 AKI is associated with high mortality in these patients 6 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Alkhalifa et al noted that thrombocytopenia was closely linked with and significantly predicted AKI 6 . Our results seem to confirm their observation; in fact, AKI in patients with COVID-19 is common, and COVID-19 AKI is associated with high mortality in these patients 6 , 32 . Many potential causes, such as interstitial nephritis, collapsing glomerulopathy, TMA, and acute tubular necrosis (ATN), may be considered possible causes of renal failure associated with COVID-19 infection 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since our study spanned from before COVID-19 (2013-2019) until 3 years during/after COVID-19 (2020-2022), patients with COVID-19 would have been only included from the last 3 years of the study, which may have created an imbalance in the distribution of patients across the study period. Nonetheless, a study by Alkhalifa, et al found that exposure to linezolid increased the likelihood of thrombocytopenia in patients with COVID-19 (chi-square p < 0.05); though, the authors did not mention the number of patients who received linezolid among the 256 included patients [39]. Therefore, it is suggested to assess the impact of a current or previous episode of COVID-19 on the incidence of thrombocytopenia in patients receiving linezolid.…”
Section: Discussionmentioning
confidence: 99%